Seroprevalence and Molecular Evidence of Coxiella burnetii in Dromedary Camels of Pakistan - Hussain, Shujaat; Saqib, Muhammad; El-Adawy, Hosny; Hussain, Muhammad Hammad; Jamil, Tariq; Sajid, Muhammad Sohail; Alvi, Mughees Aizaz; Ghafoor, Muzafar; Tayyab, Muhammad Haleem; Abbas, Zaeem; Mertens-Scholz, Katja; Neubauer, Heinrich; et al. (Frontiers in Veterinary Science, 2022)
Coxiellosis is a zoonosis in animals caused by Coxiella burnetii. A cross-sectional was conducted on 920 (591 female and 329 male) randomly selected camels (Camelus dromedarius) of different age groups from 13 districts representative of the three different ecological zones in the Province Punjab, Pakistan to determine the prevalence and associated risk factors. The blood samples were collected and tested for anti-C. burnetti antibodies using indirect multispecies ELISA. Real-time PCR was used for the detection of C. burnetii DNA to determine the prevalence in heparinized blood pools. Out of 920 investigated camels, anti-C. burnetii antibodies were detected in 288 samples (31.3%) (95% CI: 28.3-34.4%). The highest (71.4%) and lowest (1.8%) seroprevalence were detected in Rahimyar Khan (southern Punjab) and in Jhang (central Punjab), respectively. Potential risk factors associated with seropositivity of the Q fever in camels included desert area (42.5%; OR=2.78, 95% CI 1.12-3.21) summer season (35.7%; OR =2.3, 95% CI: 1.31-3.2), sex (female) (39.1; OR = 2.35, 95% CI: 1.34-2.98), tick infestation (51.3%;OR = 2.81, 95% CI: 1.34-3.02), age (˃ 10 years; 46.4%; OR = 1.56, 95% CI: 0.33-2.05) and herd size (38.5%; OR = 1.21, 95% CI: 0.76-1.54). Coxiella burnetii DNA was amplified in 12 (20%) and 1 (10%) of 60 ELISA-negative and 10 suspected camels, respectively. DNA could not be detected in ELISA positive blood pools. This study light lights the seroprevalence and associated risk factors of coxiellosis as well as its potential to spill over for animals and humans in contact with these camel herds.